Network resource stocks and flows: how do alliance portfolios affect the value of new alliance formations? - Wassmer, Ulrich; Dussauge, Pierre (Strategic Management Journal, 2012)
Abstract We examine how new network resources accessed through alliance formations interact with network resources present in a firm's alliance portfolio. We test our theoretical model using event study methodology and data from the global air transportation industry. We find that the market rewards firms forming alliances that contribute resources that can be synergistically combined with firms' own resources as well as with network resources accessed through their alliance portfolios. Our results also indicate that the market penalizes firms entering into alliances that create resource combinations that are substitutes to resource combinations deployed by existing alliance partners. Copyright © 2011 John Wiley & Sons, Ltd.